Self care behavior among patients with diabetes in Harari, Eastern Ethiopia: the health belief model perspective. - Ketema Ayele; Bisrat Tesfa; Lakew Abebe; Tizta Tilahun; Eshetu Girma (PLoS ONE, 2012)
Background Diabetes mellitus is a chronic disease that requires lifelong medical treatments and a life style adjustment. To prevent serious morbidity and mortality, it requires dedication to demanding self-care behaviors in multiple domains. The objective of this study was to identify predictors of self care behaviors among patients with diabetes. Methods From a total of 425 follow up diabetic patients, a quantitative cross sectional study was conducted among 222 of them from three different hospitals in Harar town, from March to April, 2011. The sample was taken using simple random sampling method. Data was collected using pretested questionnaire. Descriptive statistics multiple logistic regression analysis were also used to assess the predicators of self care behaviors among patients with diabetes. Result Majority of the study respondents 134 (60.4%) were female and the mean age was 49.7 (SD ± 14.7) years. More than half 147(66.2%) of them were medically diagnosed with type-2 diabetes. 208(93.7%) had general knowledge about diabetes and specific knowledge about diabetes self care 207(93.2%). Large proportion of them had moderate perceived susceptibility 174(78.4%) and severity 112(50.5%). More than half of the respondents 149(67.1%) had less perceived barrier while only 30 (13.5%) of them had high self efficacy to self care practices related to diabetes mellitus. Only 87(39.2%) followed the recommended self care practices on diabetes. Conclusions Patients with less frequent information were less likely to take diabetes self care. Patients who were more educated, middle income, had high perceived severity of diabetes and less perceived barrier to self care were more likely to take diabetes self care. To increase the self care behavior, diabetes messages should focus on severity of diabetes and how to overcome barriers for self care by segmenting the audiences based on income and educational status with increasing the frequency and reach of message on diabetes.